TREND OF VIRAL HEPATITIS CASES NOTIFIED IN THE STATE OF MATO GROSSO – BRAZIL - Santos, Débora Aparecida da Silva; Oliveira, Jaynne Soares de; Benevenuto, Vitória Carolina Ferreira; Goulart, Letícia Silveira; Olinda, Ricardo Alves de (Cogitare Enfermagem, 2023)
Objective: to analyze the time trends of viral hepatitis cases notified from 2010 to 2019 in Mato Grosso - BR. Method: an epidemiological study of the ecological type, with data collection in the Notifiable Diseases Information System. For the analysis of the time trend, a logarithmic transformation of the coefficients and the Prais-Winsten procedure for generalized linear regression analysis were performed. Results: 9,043 viral hepatitis cases were recorded: Hepatitis A (13.62%), Hepatitis B (67.19%), Hepatitis C (18.07%) and Hepatitis D (0.49%), with no Hepatitis E records. The prevalence of cases notified was higher in 2014 (12.36%) and lower in 2018 (8.16%). Hepatitis C (95% CI: 2.5; 3.4) was the only one with an increasing trend, while Hepatitis A (95% CI: -4.8; -4.6), Hepatitis B (95% CI: -0.9; -1.2) and Hepatitis D (95% CI:-0.2; -3.9) presented a decreasing trend. Conclusion: in view of their trends and incidence, it is concluded that it is indispensable to continue and improve coping actions to eradicate these diseases in the state.